Recoding: getting more out of the message by shifting reading frame and redefining codon meaning - Atkins, John; Gesteland, Raymond (Henry Stewart Talks, 2008)
Dynamic reprogramming of genetic readout, 3 broad types, Change in linearity, i.e. programmed ribosomal frame shifting, Codon redefinition, i.e. commonly "stop codons" specifying an amino acid, a standard one or selenocysteine, Discontiguity